Adam Smith and the Dark Nightingale: on twentieth-century sentimentalism - Stokes, M (Cambridge University Press, 2006)
This article reconsiders sentimentalism in the light of the writings of Adam Smith and the career of Abd al-Halim Hafiz, Egypt's 'Dark Nightingale' and film-star crooner of the 1950s and 60s. It explores competing representations of emotionality, the limits of enchantment, and the contemporary politics of nostalgia and melodrama in Egyptian public culture. Eighteenth-century sentimental theory provides a critical and productive angle on twentieth-century popular musical culture, angles that this paper explores by imagining Adam Smith watching Abd al-Halim Hafiz's first film, Lahn al-Wafā‘(1955).